»Ne le kruh, tudi vrtnice!« Potrošnja, tehnološki razvoj in emancipacija žensk v socialistični Sloveniji - Sitar, Polona (Kulturni spomin, 2017)
The book contributes new insights to the research in the field of anthropology of (post)socialism, culture of consumption, gender and memory. It is based on the testimony of interlocutors who offer an insight into the "structure of the feeling" of the socialist era through the practice of consumption, from which on the one hand the complex economic and political dynamics and diverse disciplinary regimes are being reflected and the understanding of power, resistance and emancipation on the other. Author establishes critical distance towards the approach, which discusses socialism as a totalitarianism and shows that socialist policies were not simply dictated from above, but negotiated between the state and its citizens. The female consumer in socialism did not only respond to social barriers and obstacles of history, but she also actively co-created social time. By studying how consumers interpreted and created mutual connections between material objects, moral reputation and (self)respect, the book also shows certain specific elements of Slovenian and Yugoslav development of the European countries after the Second World War.